The Last Hours/Days of Life at Hospital Versus at Home - Gaudêncio, Margarida (Gazeta Médica, 2022)
Population aging is one of the main social transformations of the 21st century, with implications for all sectors of society.The aging is accompanied by an increase in the prevalence of oncological and chronic, progressive diseases, witha high degree of functional dependence, cognitive decline, decreased quality of life and an increase in the mortality rate. The social transformation that we are witnessing implies the urgent need to plan the allocation of end-of-life supportservices, namely the development of palliative care. Worldwide, the end of life is very common in a hospital and Portugal is no exception. Several studies have demonstratedenormous variability in the quality of end-of-life care in acute hospitals. Some studies highlight the problemof this kind of care in acute hospitals, as well as the great difficulty that doctors have in deciding when to suspendcurative care and initiate palliative support. According to some data, most Portuguese prefer to die at home, however, the reality is different. The lack of access tomedical care is one of the main reasons for refusing the death process at home. Most family members, although theycan defend death at home, understand that it should occur in the hospital due to the need for permanent care and thelack of home support that guaranteed quality care. So, there is an urgent need to rethink national health policies, seeking to improve accessibility to palliative care, namelywith the creation of community/home teams, in order to improve the support of these patients at home and thusfree the acute hospitals.